Influence of cycling cadence on subsequent running performance in triathletes - Vercruyssen, F.; Brisswalter, J.; Hausswirth, C.; Bernard, T.; Bernard, O.; Vallier, J. M. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE: The purpose of this study was to investigate the influence of different cycling cadences on metabolic and kinematic parameters during subsequent running. METHODS: Eight triathletes performed two incremental tests (running and cycling) to determine maximal oxygen uptake (VO2max) and ventilatory threshold (VT) values, a cycling test to assess the energetically optimal cadence (EOC), three cycle-run succession sessions (C-R, 30-min cycle + 15-min run), and one 45-min isolated run (IR). EOC, C-R, and IR sessions were realized at an intensity corresponding to VT + 5%. During the cycling bouts of C-R sessions, subjects had to maintain one of the three pedaling cadences corresponding to the EOC (72.5 +/- 4.6 rpm), the freely chosen cadence (FCC; 81.2 +/- 7.2 rpm), and the theoretical mechanical optimal cadence (MOC, 90 rpm; Neptune and Hull, 1999). RESULTS: Oxygen uptake (VO2) increased during the 30-min cycling only at MOC (+12.0%) and FCC (+10.4%). During the running periods of C-R sessions, VO2, minute ventilation, and stride-rate values were significantly higher than during the IR session (respectively, +11.7%, +15.7%, and +7.2%). Furthermore, a significant effect of cycling cadence was found on VO2 variability during the 15-min subsequent run only for MOC (+4.1%) and FCC (+3.6%). CONCLUSION: The highest cycling cadences (MOC, FCC) contribute to an increase in energy cost during cycling and the appearance of a VO2 slow component during subsequent running, whereas cycling at EOC leads to a stability in energy cost of locomotion with exercise duration. Several hypotheses are proposed to explain these results such as changes in fiber recruitment or hemodynamic modifications during prolonged exercise.